Reality Counseling Approach to Increasing Career Woman Awareness (Case Study Love Scam) - Nakhma'ussolikhah; Iman Subasman; Lina Marliani (International Journal of Education and Humanities, 2025)
Globalization can influence changes in the lives of generations and change civilization from the real world to the virtual world. Technology movement has become a primary need at every age, from early childhood to the elderly. Needs increase materially, and conditions of need become higher with a standard income of UMR or below UMR. This research aims to increase career women's understanding of the functions and benefits of digital transformation. Research methodology with a qualitative approach to case study design. Research location in Cirebon. The research subjects consisted of 3 clients with indicators that love scam victims experienced levels of psychological loss, namely trauma and financial loss—client identity Career women aged 30 years, 32 years, and 34 years. Secondary subjects include 1 legal expert, 1 entrepreneur or economist, and 1 counselor. Data collection techniques using longitudinal observations and interviews. Data analysis technique with source triangulation. The research results found that counseling activities for love scam clients/victims resulted in psychological trauma and financial losses. Clients feel aware after 21 days of emotional approaches built through social media accounts or WhatsApp. The characteristics of a love scam are that the target is a career woman with a steady income, and the perpetrator builds a romantic relationship with the plan of marrying the client and taking property and temporary love by showing a fake identity. Clients feel hypnotized by false promises and romantic words of love with the perpetrator